2004
DOI: 10.3748/wjg.v10.i8.1098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conformal and intensity-modulated techniques for simultaneous integrated boost radiotherapy of upper esophageal carcinoma

Abstract: AIM:To compare intensity-modulated radiotherapy (IMRT) with conformal radiotherapy (CRT) by investigating the dose profiles of primary tumors, electively treated regions, and the doses to organs at risk. METHODS:CRT and IMRT plans were designed for five patients with upper esophageal carcinoma. For each patient, target volumes for primary lesions (67.2 Gy) and electively treated regions (50.4 Gy) were predefined. An experienced planner manually designed one CRT plan. Four IMRT plans were generated with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 29 publications
0
35
1
Order By: Relevance
“…For patients with neck or upper thoracic esophageal carcinoma, radiotherapy is a major treatment method now. Esophageal carcinoma is often accompanied with supraclavicular or superior mediastinal lymph node metastasis, and correlated with poor prognosis (Kawahara et al, 1998;Kurokawa et al, 2003;Xiao et al 2003;Xiao et al, 2005;Tachimori et al, 2011) Research showed that IMRT technique can not only elevate target dose, but possesse advantages of higher target conformity, higher dose uniformity and better protection of sensitive organs compared with conventional conformal radiotherapy (Nutting et al, 2001;Fu et al, 2004;Wu et al, 2004;Chandra et al, 2005;Wang et al, 2006;Fenkell et al, 2008). It was reported 5~7 intensity-modulated beams were more effective in target dose uniformity, target conformity and radiation dose to organs at risk when comparing the effect of IMRT with that of 3D-CRT on 5 cases of upper esophageal carcinoma using simultaneous integrate boost (Fu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with neck or upper thoracic esophageal carcinoma, radiotherapy is a major treatment method now. Esophageal carcinoma is often accompanied with supraclavicular or superior mediastinal lymph node metastasis, and correlated with poor prognosis (Kawahara et al, 1998;Kurokawa et al, 2003;Xiao et al 2003;Xiao et al, 2005;Tachimori et al, 2011) Research showed that IMRT technique can not only elevate target dose, but possesse advantages of higher target conformity, higher dose uniformity and better protection of sensitive organs compared with conventional conformal radiotherapy (Nutting et al, 2001;Fu et al, 2004;Wu et al, 2004;Chandra et al, 2005;Wang et al, 2006;Fenkell et al, 2008). It was reported 5~7 intensity-modulated beams were more effective in target dose uniformity, target conformity and radiation dose to organs at risk when comparing the effect of IMRT with that of 3D-CRT on 5 cases of upper esophageal carcinoma using simultaneous integrate boost (Fu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Experience with intraoperative radiation as an alternative to external beam radiation is limited. [121][122][123][124][125] Intensitymodulated radiation therapy (IMRT) is currently being investigated. Retrospective planning studies comparing three-dimensional (3D) conformal versus IMRT treatment plans for esophagus cancer have generally shown superior dose conformity and homogeneity with IMRT and reduction of radiation dose to the lungs and heart.…”
Section: Radiation Therapymentioning
confidence: 99%
“…RT dose escalation is a domain of active clinical research in oesophageal cancer, as illustrated by investigations with intensity-modulated RT (IMRT) [8][9][10][11][12][13], IMRT with protons [ 14] and the ongoing French trial CONCORDE (ClinicalTrials.gov Identifier: NCT01348217). A study in ten patients [8] showed that 66.4 Gy could be delivered with simultaneous integrated boost (SIB) IMRT, while reducing the dose to the normal heart, lung and liver, when compared to 50.4 Gy with more conventional 3D CRT plans.…”
Section: Introductionmentioning
confidence: 99%